Connection siemens PLC (programmable logic control) to labview using OPC (ole for process control) - Mahfuzah, Mustafa (2004)
The project is to enable the Siemens PLC (Programmable Logic Control) S7-300 to communicate with the Lab VIEW. The communication between S7-300 and Lab VIEW is via OPC (OLE for Process Control). Development of OPC using SIMA TIC NET OPC Server. OPC is industry standard provides real plug-and-play software technology for process control and factory automation. OPC integrate software and hardware across spectrum of vendors easily. Visualization of Festo Didactic process developed using Lab VIEW. Festo Didactic is small system which consist actuators and sensors . The process of Festo is to make hole for three different material red plastic, black plastic and metal. PROFIBUS is a medium to transfer data from PLC to Lab VIEW or Lab VIEW to PLC.